Endemic Burkitt lymphoma – an aggressive childhood cancer linked to Plasmodium falciparum exposure, but not to exposure to other malaria parasites - Smith‐Togobo, C.; Quintana, M.DP.; Moormann, A.; Hviid, L. (JOURNAL OF PATHOLOGY, MICROBIOLOGY AND IMMUNOLOGY, 2020)
Burkitt lymphoma (BL) is an aggressive non‐Hodgkin lymphoma. The prevalence of BL is ten‐fold higher in areas with stable transmission of Plasmodium falciparum malaria, where it is the most common childhood cancer, and is referred to as endemic BL (eBL). In addition to its association with exposure to P. falciparum infection, eBL is strongly associated with Epstein–Barr virus (EBV) infection (>90%). This is in contrast to BL as it occurs outside P. falciparum ‐endemic areas (sporadic BL), where only a minority of the tumours are EBV‐positive. Although the striking geographical overlap in the distribution of eBL and P. falciparum was noted shortly after the first detailed description of eBL in 1958, the molecular details of the interaction between malaria and eBL remain unresolved. It is furthermore unexplained why exposure to P. falciparum appears to be essentially a prerequisite to the development of eBL, whereas other types of malaria parasites that infect humans have no impact. In this brief review, we summarize how malaria exposure may precipitate the malignant transformation of a B‐cell clone that leads to eBL, and propose an explanation for why P. falciparum uniquely has this capacity.
Research Article
Keywords: Endemic Burkitt lymphoma; immunology; malaria; molecular microbiology; pathology of tumours; Plasmodium falciparum; PfEMP1